A Comprehensive Study of XSS Attack and the Digital Forensic Models to Gather the Evidence - Kumar, Saurabh; Pathak, S.K.; Singh, Jagendra (ECS transactions, 2022)
Cyber Crime and fraud are growing at a rapid rate and the law practitioners require proper methodology to collect the digital evidences. When the criminals use digital platform in order to commit the crime, forensic examiners apply practical frameworks and methods to collect digital evidences. Digital forensics method involves the analysis of network traffic for detecting intrusions and investigating them. Different models have been proposed for the cyber crime investigation with the merits and demerit. This research paper explores cross-site scripting (XSS) attacks, features of the existing digital forensic investigation models and discusses some of the issues related to digital forensic research.